2016
DOI: 10.1371/journal.pone.0148420
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors of Superior Mediastinal Nodal Metastasis from Papillary Thyroid Carcinoma—A Prospective Observational Study

Abstract: ObjectivesThe purpose of this study was to demonstrate the incidence rates and predictive factors of superior mediastinal lymph node (SMLN) metastasis in PTC (papillary thyroid carcinoma) patients.MethodsA prospective observational study was performed between January 2009 and January 2011. PTC patients who had tumors with a maximal diameter greater than 1 cm and clinically negative SMLNs were included in this study. Finally, a total of 217 patients who underwent total thyroidectomy with central compartment nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 21 publications
2
12
1
Order By: Relevance
“…Our study was the first study to present an analysis of predictive factors for Level VII LNM via video-assisted transcervical approach. Level VII LNM has been seen at variable incidence rates, ranging from 5.4 to 65% [7,[13][14][15], which is consistent with our study (28.73%). Previous studies suggested that many clinicopathological factors such as distant metastasis, greater total number of cervical LNM, tumor size, extrathyroidal extension, poorly differentiated carcinoma, and the age cut-off at 45 years were associated with Level VII LNM [7,8,13,14].…”
Section: Discussionsupporting
confidence: 91%
“…Our study was the first study to present an analysis of predictive factors for Level VII LNM via video-assisted transcervical approach. Level VII LNM has been seen at variable incidence rates, ranging from 5.4 to 65% [7,[13][14][15], which is consistent with our study (28.73%). Previous studies suggested that many clinicopathological factors such as distant metastasis, greater total number of cervical LNM, tumor size, extrathyroidal extension, poorly differentiated carcinoma, and the age cut-off at 45 years were associated with Level VII LNM [7,8,13,14].…”
Section: Discussionsupporting
confidence: 91%
“…Thus, we applied the method of systematic literature review to investigate the incidence, predictive factors, and prognosis of mediastinal lymph node metastases in thyroid cancer. Through comprehensive search and reasonable scientific screening, 20 studies [ 6 25 ] were included finally ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…All of the reference lists from the main articles were inspected for additional eligible studies. In total, 71 studies were retrieved and 20 studies [ 6 25 ] were finally included in the analysis according to the inclusion/exclusion criterions (detailed process of selection was shown in Figure 1(a) ).…”
Section: Methodsmentioning
confidence: 99%
“…The risk of hypoparathyroidism can reach 30% (8% to 13%) in primary procedures [10]. Transient hypocalcaemia has been reported with an incidence of up to 30% [9], rates of hypoparathyroidism (transient, 31.8%; permanent, 3.6%) with preservation of blood supply to the parathyroid glands [11]. Re-thyroidectomies associated with a higher risk of postoperative complications [11].…”
Section: Discussionmentioning
confidence: 99%
“…Transient hypocalcaemia has been reported with an incidence of up to 30% [9], rates of hypoparathyroidism (transient, 31.8%; permanent, 3.6%) with preservation of blood supply to the parathyroid glands [11]. Re-thyroidectomies associated with a higher risk of postoperative complications [11]. Revision surgery of the central compartment places the parathyroid glands at an increased risk of devascularization or inadvertent removal [9].…”
Section: Discussionmentioning
confidence: 99%